Opposing roles for Bmp signalling during the development of electrosensory lateral line organs - Campbell, Alexander S; Minařík, Martin; Franěk, Roman; Vazačová, Michaela; Havelka, Miloš; Gela, David; Pšenička, Martin; Baker, Clare V H (eLife, 2025)
The lateral line system enables fishes and aquatic-stage amphibians to detect local water movement via mechanosensory hair cells in neuromasts, and many species to detect weak electric fields via electroreceptors (modified hair cells) in ampullary organs. Both neuromasts and ampullary organs develop from lateral line placodes, but the molecular mechanisms underpinning ampullary organ formation are understudied relative to neuromasts. This is because the ancestral lineages of zebrafish (teleosts) and Xenopus (frogs) independently lost electroreception. We identified Bmp5 as a promising candidate via differential RNA-seq in an electroreceptive ray-finned fish, the Mississippi paddlefish (Polyodon spathula; Modrell et al., 2017, eLife 6: e24197). In an experimentally tractable relative, the sterlet sturgeon (Acipenser ruthenus), we found that Bmp5 and four other Bmp pathway genes are expressed in the developing lateral line, and that Bmp signalling is active. Furthermore, CRISPR/Cas9-mediated mutagenesis targeting Bmp5 in G0-injected sterlet embryos resulted in fewer ampullary organs. Conversely, when Bmp signalling was inhibited by DMH1 treatment shortly before the formation of ampullary organ primordia, supernumerary ampullary organs developed. These data suggest that Bmp5 promotes ampullary organ development, whereas Bmp signalling via another ligand(s) prevents their overproduction. Taken together, this demonstrates opposing roles for Bmp signalling during ampullary organ formation.
Keywords: signální transdukce; Acipenser ruthenus; sterlet sturgeon; developmental biology; neuromasts; vývojová regulace genové exprese; sterlet sturgeon (acipenser ruthenus); Signal Transduction; Bone Morphogenetic Proteins; Gene Expression Regulation, Developmental; proudový orgán; rybí proteiny; Lateral Line System; zvířata; lateral line; kostní morfogenetické proteiny; Fishes; ryby; ampullary organs; Bmp; Fish Proteins; Animals